Theatre and social media - Lonergan, Patrick (Macmillan education, 2016)
"Social media has become an increasingly prevalent aspect of our lives, used daily by many people. In this timely study, Patrick Lonergan examines the relationship between social media and theatre. He argues that social media is itself a performance space, analysing how it's used by both theatres and audiences and also in connection with each other"--